Outcome Of Non-Elective Covid Positive Orthopaedic Injury Procedures In Two Tertiary Care Hospitals - Syed Faraz Anwar; Ahmed Mushtaq; Syed Sheheryar Faraz (Pakistan Armed Forces Medical Journal, 2023)
Objective: To evaluate the outcome of COVID-positive orthopaedic injury patients operated as emergency cases regarding overall disease progression, laboratory parameters and fracture healing.